The Concept of Supranational EU Law: Teaching and Methodological Guide for Third-Level (Educational and Scientific) Higher Education Students. PhD in Philosophy, field of knowledge 29, specialisation 293 "International Law" - Гребенюк Д. О.; Форманюк В. В.; Бугаєць А. С.; Hrebeniuk Dmytro O.; Formaniuk Viktoriia V.; Buhaiets Alona S. (Odesa : National University "Odesa Law Academy"., 2025)
This teaching manual is intended for higher education students studying the discipline ‘Concept of EU Supranational Law’. The manual covers the content of the course by lecture and practical session topics, practical assignments, a list of topics for independent study, questions to test knowledge of the course, and a recommended list of sources. The teaching manual has been prepared in accordance with the educational programme ‘International Law’ for speciality 293 and is recommended for use in teaching when training specialists at the third (educational and scientific) level of higher education for the degree of Doctor of Philosophy.
Keywords: EU Supranational Law’; European Union; supranational legal system